Accelerating agricultural growth and poverty alleviation through public expenditure and subsidy: The experience of India - Bathla, Seema; Yu, Bingxin; Thorat, Sukhadeo; Joshi, Pramod Kumar (International Association of Agricultural Economists, 2015)
A slowdown in agricultural growth, persisted during the 1990s and early 2000s has somewhat got reversed from 2004-05. But apprehensions continue on achieving the targeted 4 percent growth amidst decelerating productivity levels and persisting poverty. To what extent has public investment and subsidy impacted agricultural growth, productivity and rural poverty? This study focuses on this issue by quantifying the effectiveness of different types of public investments and subsidies and their relative impact on agricultural growth, and employment and reduction in rural poverty in India. Results obtained from 1981 to 2011 based on a structural econometric model are differentiated with their estimated coefficients to find relative total and marginal effects of investments and subsidies on farm income and rural poverty. Bathla, Seema; Yu, Bingxin; Thorat, Sukhadeo; Joshi, Pramod K.